A Novel Method for the Growth of ZSM-5 Membranes on Stainless steel Supports by coating on Reactor Vessel with Surface-to-volume Ratio of Synthesis Governing Low Temperature Crystallization of ZSM-5 - Ana Hidayati Mukaromah; Tulus Ariyadi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
ZSM-5 membranes have been prepared using a novel seeding method. By sonicating ZSM-5 seed crystals in the presence of a stainless steel mesh of size followed by a controlled low temperature synthesis step it has been shown by XRD, FTIR, and SEM-EDX. The growth of ZSM-5 zeolite at stainless steel can be used to produce ZSM-5 zeolite membranes on reactor vessel with surface-to-volume ratio was the highest of the reactor vessel. Surface-to-volume ratio influences the heat-transfer during the synthesis, which further governs the crystallization of ZSM-5. It was found that the higher the surface-to-volume of the reactor, the more crystalline the resulting product. The result for the theoretical review paper were necessary to research the synthesis of ZSM-5 membrane based on the variation of type and size stainless steel and pretreatment of thestainless steel to use as a membrane suppport. The ratio of surface area to volume of the first reactor is the highest 1.44 influence more effective heat transfer process and the crystallinity of the zeolite ZSM-5 in the synthesis of ZSM-5 zeolite.Keywords: ZSM-5 membrane, type and size of the stainless steel, pretreatment, vessel reactor.